Ectogenesis and the Right to Life: Discussion Note on Pruski and Playford’s, “Artificial Wombs, Thomson and Abortion – What Might Change?” (Diametros, 2022)
In this discussion note on Michal Pruski and Richard C. Playford’s “Artificial Wombs, Thomson and Abortion – What Might Change?,” I consider whether the prospect of ectogenesis technology would make abortion impermissible. I argue that a Thomson-style defense may not become inapplicable due to the right to life being conceived as a negative right. Further, if Thomson-style defenses do become inapplicable, those who claim that ectogenesis would be an obligatory alternative to abortion cannot do so without first showing that fetuses have a right to life, something that Thomson assumed rather than argued for. I also include a discussion on ethical problems concerning what to do about children born from artificial wombs put there by those who looked to terminate their pregnancies because they sought to avoid parenthood.